Consciouness and Practice of Personal Hygiene among the High School Students of a Rural Area in Chattogram - Ghosh, Purnasree; Mahmud, Sayeed; Deb, Ajoy; Muzumder, Pranay Kumar; Chowdhury, Saimon Raihan Uddin; Urmi, Sharmin Sultana; Onamika, Mensila (IAHS Medical Journal, 2024)
Backround: Good health is a sign of a country's economic well-being. Personal hygiene should be maintained first and foremost for high accuracy in work, low disease suffering and disease prevention. Maintaining good hygiene is crucial because it can prevent many infectious diseases. Personal hygiene habits may have developed during childhood. Children in school are especially prone to disregarding basic personal hygiene.This study was conducted to assess the consciousness and practice of personal hygiene among the students of a rural high school in Chattogram. Materials and methods: It was a descriptive type of cross-sectionalstudy and data were collected from 314 students of Guman Mardan Pashkarhut High School in Hathazari Upazila, Chattogram from August to October 2023 by interviewer administrative questionnaire. Results: Among the respondents, most of them 141(45%) were in the age group 11-12 years. About 207 (66%) were girls and 302(96%) were Muslims. Maximum 172 (54.8%) respondents were from class VII and class 8 and 36.5% were from lower middle class. About 241(77%) heard about the term personal hygiene and maximum students, 152(63.1%) heard it from school. Most of the students 241(77%) had idea on basic requirement of personal hygiene. It was found that maximum respondents 300 (96%) know about the importance of handwashing. Among all students, 73% brush twice daily, about 307(97.77%) take shower daily in summer and 302 (96%) practiced in winter, 293 (93.31%) used a towel of their own. During tiffin time, 211(67.20%) had taken home made food. Conclusion: As most of the children neglect maintenance of personal hygiene, so their habit should be changed. It should be practiced from early childhood to lead a healthy, disease-free productive life. IAHS Medical Journal Vol 6(2), December 2023; 24-30